Upaya Meningkatkan Hasil Belajar Ips Menggunakan Metode Role Playing Pada Siswa Kelas Vi Sd Negeri 9 Bengkalis Kabupaten Bengkalis - Siti Khotimah (STAIN Bengkalis, 2017)
This research aims to: (1) know what Role playing method can be used to improve the results of Social Studies learning in Grade 6 students of SD 9 Bengkalis Regency of Bengkalis; (2) define ecological steps the implementation of Role playing method in improving the results of learning social studies grade 6 students of SD 9 Bengkalis Regency of Bengkalis. The type of this research is the Class Action Research (PKT), using Kemmis and Taggart model. The subject in this research are the students of class VI SD Negeri 9 Bengkalis Regency of Bengkalis 20 students. Test data collection technique, observation sheet, note the field, and documentation. The tests used to collect data the results of cognitive learning students, while observation sheet is used to obtain the results of the affective aspects of learning, psychomotor and activities of the teachers in the process of the implementation of Social Science lessons using Role playing method. Data analysis techniques using quantitative descriptive analysis of the data to analyze the results of cognitive learning and qualitative descriptive analysis to analyze the data result of observation. The results of the study showed that the use of Role playing method in Social Studies lessons can improve the results of learning social studies grade 6 students at SDN Bengkalis Regency of Bengkalis. Based on the test results obtained by the students at the end of every cycle and shows the improvement of Social Studies learning results. The percentage of ketutasan on pratindakan by 20%, I cycle by 60%, the cycle II by 90 percent. In the process, shows that the quality of the learning process to increase, visible from the students more active, communicative and learning atmosphere more enjoyable. In the implementation of the Role playing method, teachers need to pay attention to these things as follows: (1) the script of the drama was given to the students before the implementation of; (2) Students who observe given busy with working on WORKSHEETS; (3) the steps in Role playing method implemented as a whole in one meeting; (4) created the learning atmosphere relaxd enjoyable but under control.